Right amelia in a patient with neurofibromatosis type 1 - Aydın, Hilal (Journal of Surgery and Medicine, 2020)
Neurofibromatosis type 1 (NF1) affects many different systems such as the skeletal, endocrine, gas-trointestinal systems, as well as the skin, peripheral and central nervous systems (CNS). The NF-1 gene, located in the 11p12 region of chromosome 17, encodes a tumor suppressor protein, called neurofibromin, and is expressed in a diverse range of cell and tissue types. Neurofibromin negatively regulates the activity of an intracellular signaling molecule, p21ras (Ras), acting as a GTPase-activating protein (Ras-GAP). The Ras-GAP function of neurofibromin has been associated with various NF1-related clinical symptoms. We aimed to present a case of clinically and genetically diagnosed neurofibromatosis type 1 with a developmental anomaly in the right hand (right hand amelia). Our knowledge about whether the coexistence of these two conditions is coincidental or a result of neurofibromatosis is limited. We wanted to present this case since the coexistence of amelia and neurofibromatosis is a first.